2017
DOI: 10.4034/pboci.2017.171.26
|View full text |Cite
|
Sign up to set email alerts
|

Parental Acceptance of Various Behaviour Management Techniques used in Pediatric Dentistry: A Pilot Study in Odisha, India

Abstract: Objective: To assess the parents' acceptance towards the behavior management techniques commonly used in the pediatric dentistry. Materials and Methods: Fifty parents participated in the study. Parents were asked to view a power-point presentation on 10 behavior management techniques: 1) Voice control, 2) Tell-Show-Do, 3) Positive reinforcement, 4) Mouth prop, 5) Modelling, 6) HOME, 7) Physical restraint, 8) Oral premedication 9) N2O-O2 sedation and 10) General anesthesia. Parents were asked to arrange various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
4
0
3
Order By: Relevance
“…El uso de técnicas farmacológicas tiene cada vez mayor aprobación y menor la estabilización protectora. Los padres más permisivos y sobreprotectores aceptan, e incluso solicitan TODC farmacológicas tales como sedación o anestesia general por percibirlas como menos arriesgadas y más cómodas para sus hijos, evitándoles una situación que ellos mismos pueden considerar desagradable e incluso potencialmente traumática [32][33][34][35] . Sin embargo, los padres autoritativos tienden a rechazar estas técnicas o a tenerlas en cuenta con mucha reserva 12 .…”
Section: Evolución De La Formación Universitariaunclassified
See 2 more Smart Citations
“…El uso de técnicas farmacológicas tiene cada vez mayor aprobación y menor la estabilización protectora. Los padres más permisivos y sobreprotectores aceptan, e incluso solicitan TODC farmacológicas tales como sedación o anestesia general por percibirlas como menos arriesgadas y más cómodas para sus hijos, evitándoles una situación que ellos mismos pueden considerar desagradable e incluso potencialmente traumática [32][33][34][35] . Sin embargo, los padres autoritativos tienden a rechazar estas técnicas o a tenerlas en cuenta con mucha reserva 12 .…”
Section: Evolución De La Formación Universitariaunclassified
“…1 al 10 (1 la más aceptada, 10 la menos) siempre a partir del 5º lugar 5,19,21,34 (Figura 1). La única excepción en la literatura revisada la encontramos en Arabia Saudí 29,33 , país en el que la sedación farmacológica por vía oral ocupó el 4º puesto en el orden de aceptación de las TODC.…”
Section: Evolución De La Formación Universitariaunclassified
See 1 more Smart Citation
“…5 With advances in dentistry, a dramatic shift in the approach to managing patients has been observed. 6 Parents have an important role in the decision-making for the child. The temperament of the parents is translated into their preferences for managing their child's behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Spain, in 2010, the most acceptable techniques were tell-show-do, followed by active restraint, nitrous oxide (N 2 O) sedation, and GA, while the least accepted were the hand-over-mouth technique and papoose board (Leon et al 2010 ). In another study in India (2016), showed that sedation and GA were rated as acceptable techniques (Acharya 2017 ). This means that parental attitude towards different behaviour management techniques in paediatric dentistry is not fixed and changes over time and is affected by social and cultural changes (Jafarzadeh et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%